2020
DOI: 10.3390/buildings10070123
|View full text |Cite
|
Sign up to set email alerts
|

A MILP Optimization Method for Building Seasonal Energy Storage: A Case Study for a Reversible Solid Oxide Cell and Hydrogen Storage System

Abstract: A new method for the optimization of seasonal energy storage is presented and applied in a case study. The optimization method uses an interval halving approach to solve computationally demanding mixed integer linear programming (MILP) problems with both integer and non-integer operation variables (variables that vary from time step to time step in during energy storage system operation). The seasonal energy storage in the case study uses a reversible solid oxide cell (RSOC) to convert electricity gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Moreover, various aspects of the hydrogen economy have been investigated. These include strategies for long-range investment planning and design of future hydrogen supply chains [14]; renewable power generation and storage management [18]; and addressing the demand side [19], cost [20], uncertainty, risk, and circularity considerations [21,22], as well as multiproduct network design and planning in the context of CCUS and transportation fuel production [23,24]. The economies of scale, which require investment towards infrastructure and identifying appropriate technologies amongst the myriad available options, are of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, various aspects of the hydrogen economy have been investigated. These include strategies for long-range investment planning and design of future hydrogen supply chains [14]; renewable power generation and storage management [18]; and addressing the demand side [19], cost [20], uncertainty, risk, and circularity considerations [21,22], as well as multiproduct network design and planning in the context of CCUS and transportation fuel production [23,24]. The economies of scale, which require investment towards infrastructure and identifying appropriate technologies amongst the myriad available options, are of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…Although RSOC technology has been developed for some years [9], the high decay rate appeared in the SOEC operating mode has always been a major obstacle hindering the development of RSOC. It is found that interfacial resistance in the oxygen electrode is much higher compared with that in fuel electrode, which is considered as one of the major reasons for resulting in performance decay.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed solution would economically favour household consumers too, since the energy export prices are usually lower than the import ones, making the direct sale of renewable energy surplus disadvantageous. Rather, according to an economic optimisation of energy use, when the price is low, it results in the cost-effective conversion of the electricity from the grid to store hydrogen and then its internal consumption to satisfy the demand when the grid energy cost is high [19]. However, rSOC technology can be introduced in a wider framework.…”
Section: Introductionmentioning
confidence: 99%